1992
DOI: 10.1152/jappl.1992.73.5.1743
|View full text |Cite
|
Sign up to set email alerts
|

Stroke volume and cardiac output decrease at termination of obstructive apneas

Abstract: Patients with obstructive sleep apnea (OSA) experience repetitive nocturnal oscillations of systemic arterial pressure that occur in association with changes in respiration and changes in sleep state. To investigate cardiac function during the cycle of obstruction (apnea) and resumption of ventilation (recovery), we continuously measured left ventricular stroke volume (LVSV) and mean arterial blood pressure (MAP) during non-rapid-eye-movement sleep in six males with severe OSA (apnea/hypopnea index > or = 30 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
68
0
6

Year Published

1994
1994
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(82 citation statements)
references
References 0 publications
7
68
0
6
Order By: Relevance
“…A possible role for an increase in cardiac output at the release of obstruction as a cause of the postapnoeic increase of Ppa, as previously suggested [3,5], can no longer be upheld, in the light of the recent studies which have shown a decrease in cardiac output in the immediate post-apnoeic period [29,30].…”
Section: Discussionmentioning
confidence: 92%
“…A possible role for an increase in cardiac output at the release of obstruction as a cause of the postapnoeic increase of Ppa, as previously suggested [3,5], can no longer be upheld, in the light of the recent studies which have shown a decrease in cardiac output in the immediate post-apnoeic period [29,30].…”
Section: Discussionmentioning
confidence: 92%
“…13 Combined hypercapnic and hypoxic stimulation produces a synergistic increase in SNA that is more than additive. 12 Upon resumption of ventilation at airway reopening, and often coincident with arousal from sleep, there is a large surge in HR (tachycardia) 14 superimposed upon hypoxia-induced peripheral vasoconstriction, resulting in a large increase in BP. Resumption of ventilation also marks the abrupt decline in SNA and this is most likely due to inhibition via stimulation of pulmonary afferents.…”
Section: Hemodynamic Effects Of Osamentioning
confidence: 99%
“…Οι Garpestad και συνεργάτες [183] χρησιμοποιούσαν ένα μη επεμβατικό σύστημα πυρηνικής ιατρικής που επιτρέπει να μετρηθεί ο όγκος της αριστερής κοιλίας και ο όγκος της συστολικής εξώθησης κατά τη διάρκεια κάθε καρδιακού κύκλου. Κατά τις αποφρακτικές άπνοιες, ο τελοσυστολικός όγκος της καρδιάς αυξάνει προοδευτικά με σύγχρονη μείωση του εξωθούμενου συστολικού όγκου αίματος [183].…”
Section: καρδιακή παροχή συστολικού κλάσματος εξώθησηςunclassified
“…Κατά τις αποφρακτικές άπνοιες, ο τελοσυστολικός όγκος της καρδιάς αυξάνει προοδευτικά με σύγχρονη μείωση του εξωθούμενου συστολικού όγκου αίματος [183]. Στον ίδιο χρόνο, όπως περιγράψαμε προηγουμένως, η καρδιακή συχνότητα και η ΑΠ αυξάνουν.…”
Section: καρδιακή παροχή συστολικού κλάσματος εξώθησηςunclassified
See 1 more Smart Citation